"I have been in an earthquake": Epistemic upheaval in Richard Hughes' A High Wind in Jamaica. (June 2019) - van Schalkwyk, Simon; Titlestad, Michael
Published in 1929, Richard Hughes' A High Wind in Jamaica was praised by reviewers and critics across the spectrum of the British and American literary scenes (among them Rebecca West, Ford Madox Ford, Vita Sackville-West, Cyril Connelly, John Masefield, Hugh Walpole, and Arnold Bennett). At the same time, its readers were generally shocked by its portrait of child psychology ("the mind of the child"). While several critics applauded its realism, the record of its reception suggests that it induced — what one critic referred to as — "a sort of mental panic". This article considers aspects of Hughes' "new psychology", which derived largely from the writings of Freud and the Freudians. Reading the novel and Freud in counterpoint, the argument concludes that — while Hughes constructs A High Wind in Jamaica as a rejoinder to the ideological logic of the imperial romance — in inscribing Freudian "primitivism" it reiterates colonial assumptions about "civilization".